2020
DOI: 10.1080/21505594.2020.1771980
|View full text |Cite
|
Sign up to set email alerts
|

Development of a TaqMan-probe-based multiplex real-time PCR for the simultaneous detection of emerging and reemerging swine coronaviruses

Abstract: With the outbreak of the recent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in 2019, coronaviruses have become a global research hotspot in the field of virology. Coronaviruses mainly cause respiratory and digestive tract diseases, several coronaviruses are responsible for porcine diarrhea, such as porcine epidemic diarrhea virus (PEDV), porcine deltacoronavirus (PDCoV), and emerging swine acute diarrhea syndrome coronavirus (SADS-CoV). Those viruses have caused huge economic losses and are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 58 publications
1
49
0
Order By: Relevance
“…including porcine epidemic diarrhea virus (PEDV), swine acute diarrhea syndrome coronavirus (SADS-CoV), transmissible gastroenteritis virus (TGEV), and porcine delta coronavirus (PDCoV), are prevalent in pig populations and cause huge economic losses. [4][5][6][7] Porcine enteric coronaviruses have similar epidemiological, clinical, and pathological characteristics. Infection with TGEV and PEDV is characterized by severe diarrhea, vomiting, and dehydration, leading to high morbidity and mortality in piglets.…”
mentioning
confidence: 99%
“…including porcine epidemic diarrhea virus (PEDV), swine acute diarrhea syndrome coronavirus (SADS-CoV), transmissible gastroenteritis virus (TGEV), and porcine delta coronavirus (PDCoV), are prevalent in pig populations and cause huge economic losses. [4][5][6][7] Porcine enteric coronaviruses have similar epidemiological, clinical, and pathological characteristics. Infection with TGEV and PEDV is characterized by severe diarrhea, vomiting, and dehydration, leading to high morbidity and mortality in piglets.…”
mentioning
confidence: 99%
“…We found that Jiang established an RT-PCR sensitivity of 10 4 copies/µL [ 73 ], and Pan established an RT-qPCR sensitivity of 10 2 copies/µL [ 74 ]. In this study, the sensitivity of the RT-RAA was 10 1 copies/µL, which was 1000 times for RT-PCR and 10 times for RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the amplification efficiency of different primers and probes, the annealing temperature of the primers was set at 57 • C, the annealing temperature of the probe was set at 67 • C. Notably, in this developed assay, the primer/probe set of BVDV showed the lowest amplification. One possible explanation is that the fluorescence of Cy5 was the weakest and very susceptible to interference from other fluorophores due to its own physical properties (30). Despite the optimization such as primer/probe concentration and annealing temperature, the improvement effect was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional RT-PCR and PCR have been widely applied for pathogen detection. However, this method is only suitable for infection by a single pathogen, and time-consuming ( 29 , 30 ). As bovine respiratory disease syndrome is mainly caused by co-infection of multiple pathogens, it is urgent to develop a rapid and convenient detection method to simultaneously the pathogens causing BRDC.…”
Section: Discussionmentioning
confidence: 99%